Implementing organic amendments to enhance maize yield, soil moisture, and microbial nutrient cycling in temperate agriculture - Foster, Erika J., author; Cotrufo, M. Francesca, advisor; Comas, Louise, committee member; Rhoades, Charles, committee member; Wallenstein, Matthew D., committee member (Colorado State University. Libraries, 2018)
To sustain agricultural production into the future, management should enhance natural biogeochemical cycling within the soil. Strategies to increase yield while reducing chemical fertilizer inputs and irrigation require robust research and development before widespread implementation. Current innovations in crop production use amendments such as manure and biochar charcoal to increase soil organic matter and improve soil structure, water, and nutrient content. Organic amendments also provide substrate and habitat for soil microorganisms that can play a key role cycling nutrients, improving nutrient availability for crops. Additional plant growth promoting bacteria can be incorporated into the soil as inocula to enhance soil nutrient cycling through mechanisms like phosphorus solubilization. Since microbial inoculation is highly effective under drought conditions, this technique pairs well in agricultural systems using limited irrigation to save water, particularly in semi-arid regions where climate change and population growth exacerbate water scarcity. The research in this dissertation examines synergistic techniques to reduce irrigation inputs, while building soil organic matter, and promoting natural microbial function to increase crop available nutrients. The research was conducted on conventional irrigated maize systems at the Agricultural Research Development and Education Center north of Fort Collins, CO. The first field experiment tested a temporally limited irrigation strategy with high application rates of organic amendments (30 Mg ha-1) to increase soil moisture, N and P retention, and enhance soil microbial activity. The experiment used biochar created from bio-energy production. The control plots contained 1.49% total soil carbon, and biochar addition increased total carbon to 2.67%. The biochar also had variable impacts on microbial extracellular enzyme activities, causing a 40% reduction in β-1,4-glucosidase and phosphatase activities, with repercussions for hydrolysis of soil P and cellulose. However, the biochar amendment did not enhance yield. This field experiment also found that the limited irrigation technique reduced water inputs by 30% while maintaining yield. The second experiment of the dissertation determined the mechanism behind the decrease in extracellular enzymatic activities after biochar addition. Through a combination of a Bradford protein assay and a fluorometric assay of potential enzymatic activities, the pine wood biochar adsorbed and reduced both β-glucosidase and acid phosphatase activities by 75-100% relative to a control soil. Though highly variable, depending upon pH, the main factor influencing activity levels was the solid phase. The high temperature biochar had a large surface area within micropores. The substrate can diffuse into the micropores, where it is inaccessible to large enzymes; there is lower catalysis of those substrates, which indicates potentially lower nutrient release in the soil. Finally, to examine the agronomic efficacy of biochar, a second maize field trial was developed also implementing full and limited irrigation. This experiment incorporated an engineered coconut hull biochar, characterized by a neutralized pH, removed toxins from the surface, and homogenized pores. The biochar was banded directly onto the seed row at a low application rate (0.8 Mg ha-1). Additionally, a surface applied plant growth promoting P solubilizing bacterial inoculum was tested alone, and in combination with biochar. To determine the efficacy of these amendments to improve soil nutrient availability and maize yields, the soil nutrient supply, crop nutrient concentration and accumulation, and soil bacterial community composition were measured. The bacterial community data was analyzed using a cutting-edge technique based on Exact Sequence Variants to analyze single nucleotide differences, enhancing comparability with future studies. In this experiment the biochar increased soil available K and S which correlated to crop uptake, shifted the early season microbial community, and increased by 20% over the control (+1.95 Mg ha-1). The inoculum and combination treatments did not impact yield, but in these plots we observed the presence of bacterial families that were added in the original inoculum. Overall this work emphasized the efficacy of precision management strategies with biochar application to enhance yield. This dissertation work underlines the importance of contentiously selecting specific amendment type, application rate and method to achieve either agronomic or environmental benefits. Continued research with synergistic approaches will help to develop best practices within the region to manage agroecosystems for improved resilience.
Keywords: biochar; exact sequence variant; irrigation management; corn; 16S bacterial community analysis; extracellular enzymes